2022
DOI: 10.3390/life13010043
|View full text |Cite
|
Sign up to set email alerts
|

Parkia speciosa Hassk. Empty Pod Extract Prevents Cardiomyocyte Hypertrophy by Inhibiting MAPK and Calcineurin-NFATC3 Signaling Pathways

Abstract: Cardiac hypertrophy is an early hallmark during the clinical course of heart failure. Therapeutic strategies aiming to alleviate cardiac hypertrophy via the mitogen-activated protein kinase (MAPK)/calcineurin-nuclear factor of activated T-cells (NFAT) signaling pathway may help prevent cardiac dysfunction. Previously, empty pod ethanol crude extract of Parkia speciosa Hassk was shown to demonstrate protective effects against cardiomyocyte hypertrophy. Therefore, the current study aimed to investigate the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Oxidative stress and inflammation are the culprits in almost all diseases. Increased dietary intake of polyphenol-rich foods reported to significantly lower the prevalence of diseases owing to its antioxidant properties [ 51 , 52 ]. G. celebica were evaluated by different in vitro antioxidant assays like 2,2-diphenyl-1-picrylhydrazyl (DPPH), folin-Ciocalteu (FCA), lipoxygenase enzyme inhibition, ferric ion reducing antioxidant power (FRAP), ferrous ion chelating (FIC), ferric reducing power (FRP), and 2,2-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and free radical scavenging (FRS) capacity assays.…”
Section: Pharmacological Effects Of Garcinia Celebicamentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress and inflammation are the culprits in almost all diseases. Increased dietary intake of polyphenol-rich foods reported to significantly lower the prevalence of diseases owing to its antioxidant properties [ 51 , 52 ]. G. celebica were evaluated by different in vitro antioxidant assays like 2,2-diphenyl-1-picrylhydrazyl (DPPH), folin-Ciocalteu (FCA), lipoxygenase enzyme inhibition, ferric ion reducing antioxidant power (FRAP), ferrous ion chelating (FIC), ferric reducing power (FRP), and 2,2-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and free radical scavenging (FRS) capacity assays.…”
Section: Pharmacological Effects Of Garcinia Celebicamentioning
confidence: 99%
“…Platelet aggregation may lead to serious conditions such as arterial thrombus formation event, which eventually cause ischaemic stroke and acute myocardial infarction [ 62 ]. The effectiveness of certain polyphenolics derived from plants has greatly linked in the prevention of cardiovascular diseases [ 52 , 63 ]. Anti-platelet aggregation activity was reported in G. celebica plant.…”
Section: Pharmacological Effects Of Garcinia Celebicamentioning
confidence: 99%
“…Kaempferol (3,4 ,5,7-tetrahydroxyflavone) (Figure 1), a yellow crystalline compound, is a flavonol which is rich in various plants such as tea, broccoli, tomatoes [22], and beans (e.g., bitter bean) [23]. Many studies have demonstrated the pharmacological activities of this compound in various pathological conditions, such as cardiovascular disease [6,13] and cancer [24].…”
Section: Introductionmentioning
confidence: 99%